Project Based Learning: Development of Monitoring Wind Direction and Speed with Solar Power as Learning Media - Setiyo, Setiyo; Soleh, Asep Muhamad; Sunardi, Sunardi; Kusumastuti, Mayang Enggar; Andeni, Afra Nabilah (Yayasan Sembilan Pemuda Indonesia, 2024)
Learning in the classroom needs appropriate methods and packaging to get good results for students. This study aims to determine the differences in learning methods using project-based practical learning and regular learning. The study was carried out using quantitative methods by conducting evaluations and interviews with students. Data processing uses the Manova test statistical data processing application. The sample from this research was students in the 3rd semester of the Airport Engineering Technology Study Program. From the results of data processing, it can be seen that there are differences in terms of understanding, collaboration and learning outcomes between students who use project-based learning methods and those who use regular learning systems. Project-based learning methods have fostered better understanding and collaboration. We hope that with the results of this research, educators will use project-based learning methods more often to foster understanding and collaboration between students in the campus environment.